If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 2) = 8(x + -1) Reorder the terms: (2 + 3x) = 8(x + -1) Remove parenthesis around (2 + 3x) 2 + 3x = 8(x + -1) Reorder the terms: 2 + 3x = 8(-1 + x) 2 + 3x = (-1 * 8 + x * 8) 2 + 3x = (-8 + 8x) Solving 2 + 3x = -8 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 2 + 3x + -8x = -8 + 8x + -8x Combine like terms: 3x + -8x = -5x 2 + -5x = -8 + 8x + -8x Combine like terms: 8x + -8x = 0 2 + -5x = -8 + 0 2 + -5x = -8 Add '-2' to each side of the equation. 2 + -2 + -5x = -8 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = -8 + -2 -5x = -8 + -2 Combine like terms: -8 + -2 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| 4-5t=6+3t | | 6x=8+5x | | 4y^2+8y=-4 | | (-38+x)(2+-1x)=0 | | Cosx=5sinx | | 3+ln(2x)=0 | | Q(y+2)=y | | 3x+x+3=10x-6x+3 | | 3r-7r= | | (16+14)+9= | | 5w=10-6 | | -2(3x-5+2y)= | | -4(2w+2)-w=28 | | g(x)=x^2-121 | | 3n+6-7n=33-12n+21 | | q^2+2p^2=100 | | 7(4-t)=-4 | | Y^2+3y-504=0 | | -3p-6(-4p-3)=-p+7(1+3p) | | 9y^2+54y-144=0 | | 6b-2b=48 | | 6x^2-87x+12=0 | | 59=3x-7 | | 2-16x+36y=0 | | 1.3+8.5=9.8 | | 8-4x+12y=0 | | 1.3+5.8= | | 6(3n+1)-3(-1+2n)=n+2n | | 6+2s=148-s | | .2+40= | | x+1-12=-9 | | 5p+7=1 |